THE EFFECT OF GRASP (GUIDE READING AND SUMMARY PROCEDURE) ON THE STUDENTS ABILITY READING COMPREHENSION IN NARRATIVE TEXT OF ELEVENTH GRADE AT SMK TAMANSISWA BINJAI - witari virgoani; Efrini Panjaitan (STKIP Budidaya Binjai, 2021)
The objective of this study is to find out the effect of using GRASP Strategy on The Students Ability in Reading Comprehension at Narrative Text of Eleventh Grade Student of SMK Tamansiswa Binjai. This quantitative research used experimental study and took samples by cluster random sampling technique. The samples were consisted of two groups, they were class XI RPL which consist of 32 students as experimental group and class XI TKJ-2 which consist of 32 students as control group at SMK Tamansiswa Binjai. The writer used multiple choice test as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table, (t0 = 7.24 > tt = 1.669). Therefore, the hypothesis proposed by the writer was accepted. In other words, using GRASP Strategy significantly affects the students’ reading skill of the eleventh grade students at SMK Tamansiswa Binjai.